Epitaxial Growth of CsPbX3 (X = Cl, Br, I) Perovskite Quantum Dots via Surface Chemical Conversion of Cs2 GeF6 Double Perovskites A Novel Strategy for the Formation of Leadless Hybrid Perovskite Phosphors with Enhanced Stability - Wei, Yi (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.